Comparative evaluation of facial attractiveness by laypersons in terms of facial proportions and equate it's deviation from divine proportions - A photographic study - Romilkumar Shah; Rahul Nair (Elsevier, 2022)
Introduction: The human face is a unique structure and says a lot about an individual even more than what the body indicates about the overall attractiveness. Facial attractiveness is an important key to social interactions and individual behavior. The human body is made in such a way that it follows a specific mathematical proportion called the Golden Proportion. In order for any two parts to be aesthetically proportionate, the ratio between them should be 1.618. Studies have shown that aesthetically pleasing profiles have facial proportions and ratios that closely resemble the golden proportions. Aim: To evaluate the perception of esthetic facial photographs by laypersons and compare these with the accepted norms of divine proportions to find for any deviations from those norms. Methodology: Forty subjects having normal soft tissue profile angle, as evaluated using Burstone's method, were selected to be photographed for the study. All the photographs were taken using DSLR Camera and under a standard photographic setup. All the photographs were edited and compiled into a PowerPoint presentation. The edited photographs on the PowerPoint presentation were displayed to 302 evaluators. These evaluators were asked to score each photograph according to a visual analogue scale with markings from 0 to 10 (with 0 being least attractive and 10 being most attractive) according to their attractiveness. All the scored photos were then grouped into three categories viz. Very attractive, Average attractive and Least attractive. Three horizontal proportions and three vertical proportions were assessed digitally in all the photographs and any deviations from the golden proportion were assessed. Results: It was found that none of the three groups followed golden proportions accurately. However the Very Attractive group showed closest resemblance to the golden proportion as compared to the other two groups. Amongst all the horizontal and vertical proportions in the Very Attractive group, Interchelion to Interalar proportion (Ch:Ln) was the one that showed maximum deviation from the divine proportion (mean value 1.38 ± 0.15). Rest of the other horizontal and vertical proportions in the Very Attractive group were close enough to the divine proportion. However the difference between the proportions amongst the three groups was not statistically significant. Comparison between the three groups showed that Very Attractive faces showed the least deviations from the golden proportions whereas least attractive faces showed most deviations from the golden proportions. Conclusion: The findings of this study state that the perception of aesthetically pleasing faces by laypersons do not accurately follow golden proportion but are close enough to it. The faces not showing golden proportions are perceived as less attractive.